PENGARUH FEAR OF MISSING OUT, ADIKSI SMARTPHONE, DAN LONELINESS TERHADAP PERILAKU PHUBBING PADA GENERASI Z KOTA TANGERANG BANTEN - Asuro, Dewi Putri Aprianti; Saloom, Gazi (Universitas Gunadarma, 2024)
The presence of smartphones and their features provides various conveniences. But behind the convenience presented, smartphones can cause phubbing behavior problems. This study aims to test whether there is an effect of fear of missing out (FoMO), smartphone addiction, and loneliness on phubbing behavior. This study used a quantitative approach. The research sample amounted to 340 Generation Z aged 15 to 27 years who owned smartphones and were domiciled in Kota Tangerang. Sampling using a non-probability sampling technique, namely convenience sampling. The measuring instruments used in this study were The Phubbing Scale (PS) instrument scale, the Trait-State Fear of Missing Out (FoMO) scale (T-SFoMOS), a modification of the smartphone addiction scale-short version (SAS-SV), and A Rasch-Type Loneliness Scale. This study used multiple regression analysis techniques. The results of the analysis proved that the hypothesis was accepted, namely, there was a significant influence of the variables fear of missing out (FoMO), smartphone addiction, and loneliness on phubbing behavior by 0.841 or 84.1%, and the remaining 15.9% was influenced by other variables outside this study.